Prognostic Impact of Inflammatory Markers PLR, LMR, PDW, MPV in Medullary Thyroid Carcinoma - Li, Canxiao; Zhang, Han; Li, Shijie; Zhang, Daqi; Li, Jingting; Dionigi, Gianlorenzo; Liang, Nan; Sun, Hui (Frontiers in Endocrinology, 2022)
Background: Neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), lymphocyte-to-monocyte ratio (LMR), mean platelet volume (MPV), and platelet distribution width (PDW) have been used as prognostic biomarkers in various cancers. We aim to investigate the relationship between the above inflammatory indices, clinicopathological features, and postoperative calcitonin (Ctn) progression in medullary thyroid carcinoma (MTC). Methods: Sixty-eight patients diagnosed with MTC who underwent surgery at our institution between 2009 and 2020 were retrospectively evaluated. Areas under the receiver operating characteristic curves (ROC) and logistic regression were applied to explore the potential risk factors. Results: PDW was predictive of lymph node metastasis (LN) (AUC=0.645, P=0.044), PLR, PDW, and MPV were predictive of capsule invasion (AUC=0.771, P=0.045; AUC=0.857, P=0.008; and AUC =0.914, P=0.002, respectively), and MPV and LMR were predictive of postoperative Ctn progression (AUC=0.728, P=0.003; AUC=0.657, P=0.040). Multivariate analysis revealed that PDW≤16.4 ((OR=7.8, 95% CI: 1.532-39.720, P=0.013)) and largest tumor size ≥1 cm (OR=4.833, 95% CI: 1.514-15.427, P=0.008) were potential independent risk factors for lateral LN metastasis. We also found that, MPV≤8.2(OR=13.999, 95% CI: 2.842-68.965, P=0.001), LMR≤4.7 (OR=4.790, 95% CI: 1.034-22.187, P=0.045), and N1 (OR=45.890, 95%CI:3.879-542.936, P=0.002) were potential independent risk factors for postoperative Ctn progression. In addition, compared with the single indicator, the appropriate combination of MPV and LMR could improve the specificity and sensitivity of predicting postoperative Ctn progression. Conclusions: PLR, LMR, PDW, and MPV were associated with clinicopathological features and postoperative Ctn progression in MTC, suggesting that those inflammatory indices might be potential biomarkers of MTC.